Nano transfersomes vesicles of raloxifene HCl with sorbitan 80: formulation and characterization - Mahmood, Sayed; Chatterjee, Bappaditya; Mandal, Uttam Kumar (Medwin, 2018)
Lipid vesicles in the nano range with ionic and nonionic surfactants are known as transfersomes. The presence of surfactant in the bilayer structure makes the vesicles very flexible in nature and helps them to permeate through the stratum corneum. The purpose of this research was to develop and characterize a transfersomal formulation of raloxifene HCl to deliver it into systemic circulation through the transdermal route. The transfersomal formulation was prepared by the rotary evaporation method with phospholipon 90G and sorbitan 80. The particle size, zeta potential and polydispersity index (PDI) of the formulation were measured. The drug entrapment efficiency (EE%) of the vesicles was determined by an indirect ultracentrifugation method. Differential scanning calorimetry (DSC), ex-vivo skin permeation study, field emission scanning electron microscope (FESEM), high resolution transmission electron microscope (HRTEM) and confocal laser scanning microscopy (CLSM) study were carried out as parts of advanced characterization of the developed formulation. The vesicles were found to have an average particle size of 95.1±1.05nm with a PDI value of 0.162±0.01 and zeta potential of +17.62±0.29 mV. EE% was recorded up to 90.9±1.15. Transdermal flux (J = 4.66±0.79 μg/cm2hr) of the developed formulation showed a favorable value required for the formulation efficacy. FESEM and TEM study results proved the spherical and round structures of the vesicles. DSC showed that the raloxifene was in the non-crystal form and was enclosed in the lipid bilayer. CLSM study proved the distribution of the drug in the stratum corneum, viable epidermis and dermis with high fluorescence intensity. The developed nano transfersomes of raloxifene HCl with sorbitan 80 showed encouraging results and can be further investigated for in vivo efficacy.